2014
DOI: 10.1002/ijc.28948
|View full text |Cite
|
Sign up to set email alerts
|

Bone-induced c-kit expression in prostate cancer: A driver of intraosseous tumor growth

Abstract: Loss of BRCA2 function stimulates prostate cancer (PCa) cell invasion and is associated with more aggressive and metastatic tumors in PCa patients. Concurrently, the receptor tyrosine kinase c-kit is highly expressed in skeletal metastases of PCa patients and induced in PCa cells placed into the bone microenvironment in experimental models. However, the precise requirement of c-kit for intraosseous growth of PCa and its relation to BRCA2 expression remain unexplored. Here, we show that c-kit expression promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…1 ). Similar observations were previously made by others for pancreatic [11] , NSCLC [38] or prostate cancer cells [39] . Beside this variation we observed that there were always one or two cell lines with extreme values, as for instance for H520 cells characterized by an extreme over-expression of SCF, and H23 and LnCap both showing a very low expression when compared to the other cell lines ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…1 ). Similar observations were previously made by others for pancreatic [11] , NSCLC [38] or prostate cancer cells [39] . Beside this variation we observed that there were always one or two cell lines with extreme values, as for instance for H520 cells characterized by an extreme over-expression of SCF, and H23 and LnCap both showing a very low expression when compared to the other cell lines ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…[21], [52], [57] CD117 expression in many cancers is associated with shorter disease survival and metastasis and is increased with cancer progression in prostate cancer patients with the highest levels of CD117 staining seen in bone metastases. [21], [57]- [59] However, the opposite is true in myeloid/erythroid cancers, whose patients have improved or unchanged prognosis when CD117 is expressed. [60] This may be partially due to biological differences between hematologic malignancies and solid tumors in Harris 18 which some genes and miRNA have opposite functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported LCM and DNA sequencing from a frozen bone metastasis of a mCRPC patient [ 49 ], or gene expression analysis of total RNA directly obtained from snap-frozen bone marrow biopsies largely replaced by tumor [ 50 ] or frozen bone metastatic cores isolated at autopsy [ 12 , 13 , 51 , 52 ]. However, in addition to our earliest analysis in a few PCa bone metastasis [ 53 ], the present study is the only report that, to the best of our knowledge, uses LCM and aRNA amplification for gene analysis of limited number of tumor cells microdissected from FFPE BMBx obtained from living mCRPC patients. In spite of better RNA recovery and quality ascribed to frozen tissue [ 43 , 44 , 54 ], we found that its use as homogenate might be inadequate for gene expression analysis of PCa bone micrometastasis, due to dilution of PCa-specific genes by other genes expressed predominantly by bone cells.…”
Section: Discussionmentioning
confidence: 99%